Magnetic Metal–Organic Frameworks for Efficient Carbon Dioxide Capture and Remote Trigger Release. Issue 9 (3rd January 2016) - Li, Haiqing; Sadiq, Muhammad Munir; Suzuki, Kiyonori; Ricco, Raffaele; Doblin, Christian; Hill, Anita J.; Lim, Seng; Falcaro, Paolo; Hill, Matthew R.
Abstract : Magnetic metal–organic framework (MOF) composites show highly efficient CO2 desorption capacities upon their exposure to an alternating magnetic field, demonstrating a magnetic induction swing strategy for potentially low‐energy regeneration of MOF adsorbents.